PENERAPAN TEKNOLOGI KOMPUTER GRAFIS UNTUK INOVASI DESAIN BATIK DI USAHA BATIK PANDANSARI, PLUPUH, SRAGEN - Theresia Widiastuti; Apika Nurani Sulistyati; Setyawan; Darwoto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Making batik designs requires the ability to visualize ideas for motifs or decorations. This process relies on the ability to move the visual processing process which was originally still an idea into something real, which can be seen in the form of an image. The ability to visualize is important because from this process motifs, patterns and decorations can be created. This work is quite complicated, requires precision, patience and takes time. When there are many orders, the work of drawing motifs must be faster. One solution to speed up making drawings is to use computer graphics to help create innovative written batik designs in a shorter time than if done manually. Through community service activities, the application of computer graphics technology for batik design innovation at the Pandansari Plupuh Sragen Batik Business uses training methods delivered offline and online. This is because both trainers and participants take time out of their busy work schedules. The participants are employees in the design department who are able to use computers. Through one face-to-face meeting for explanation and four online meetings for practice which aims to improve participants' skills in making various kinds of motifs. The result is a new design that can be completed relatively quickly compared to if it was done manually.